Consumption of Energy Drinks Among Lebanese Youth: A Pilot Study on the Prevalence and Side Effects - Itany, Manal (Int J High Risk Behav Addict, 2014)
BACKGROUND: The new millennium has been together with a variety of synthetic and caffeinated high-energy drinks targeting the youth market. Energy drinks raise the level of energy and their consumption has been increased significantly worldwide. OBJECTIVES: This research aimed to determine patterns of energy drink consumption and to assess the prevalence of adverse side effects among energy drink users. PATIENTS AND METHODS: A pilot cross-sectional study survey was undertaken on students aged between 13 and 30 years in private and public schools and universities in Lebanon over 5 months. A self-administered questionnaire was used inquiring about sociodemographic characteristics, consumption patterns, attitudes and beliefs about energy drinks. Bivariate and multivariate analyses were conducted. Data was analyzed using SPSS 17. RESULTS: We studied 1500 students (mean age: 18.92 ± 1.85; 51.3% were males). The overall prevalence of energy drinks consumption was 63.6% (60.5% were males), among which 50.5% used alcoholic energy drinks. Respondents indicated that most consumed energy drinks were “Red Bull” and “Boom Boom” (70.9% and 51.5% respectively). In total, 64.5% of participants believed the effect of these drinks in energizing the body, and 72.7% believed that they can stimulate intellectual capacities. In addition, 29.6% of consumers experienced at least one adverse effect, where tachycardia was reported in 21.1% of cases. On the other hand, desired effects felt after consumption were mostly pleasure (33.8%). Males had a 3-time more risk of consuming such drinks compared to females (OR: 0.381, P < 0.001; 95% CI: 0.300-0.484). Additionally, this analysis demonstrated a significant association between energy drinks consumption and regions outside Beirut (OR: 1.401, P: 0.006; 95% CI: 1.103-1.781), medical field of work (OR: 0.376, P: 0.010; 95% CI: 0.179-0.790) and higher personal income (OR: 1.317, P < 0.001; 95% CI: 1.117-1.553). CONCLUSIONS: This study showed a high prevalence of energy drinks consumption among youth. The current results highlight the importance of education to prevent the consumption of energy drinks in excessive quantities and modifying some wrong perceptions regarding the benefits of energy drinks in youth.